Study of the Production, Import, and Export of Intermediate Inputs in Ecuador’s Manufacturing Sector and their impact on the Ecuadorian Incorporated Product - Jorge García Regalado; Rina Bucaram Leverone; Víctor Quinde Rosales; Anthony Limones Salazar (Migration Letters, 2023)
This paper seeks to identify the production, import, and export of intermediate inputs of the manufacturing sector in Ecuador, for which we worked with secondary data, using an exploratory and descriptive study, data were collected from the economic sectors of ISIC 29, 30, and 10. Subsequently, we proceeded to use the econometric technique of panel data, included in a set of multivariate tools for the analysis of the dependence between variables. As a result, a strong relationship of imports for the final process of good was evidenced, generating structural imbalances with this practice. It was possible to corroborate a high dependence on intermediate inputs, which affects the internal development of the industry and the Ecuadorian productive matrix.